Characteristic Aroma Compounds in Two New Vitis vinifera Cultivars (Table Grapes) and Impact of Vintage and Greenhouse Cultivation - Duan, L.-L.; Pan, Q.-H.; Tang, X.-J.; Yang, Q.; Jiang, R.; Shi, Y.; Duan, C.-Q. (South African Journal of Enology and Viticulture, 2016)
‘Zaoheibao’ (a red tetraploid hybrid) and ‘Wuhecuibao’ (a white triploid hybrid) grapes have been obtained from Guibao♀ (diploid, Vitis vinifera) × Zaomeigui♂ (diploid, V. vinifera) and Guibao♀ (diploid, V. vinifera) × Wuhebaijixin♂ (triploid, V. vinifera) respectively. Aroma characterisation of the two new table grape cultivars was firstly done by the investigation of volatile compounds. The influence of greenhouse cultivation and vintage on berry aroma was studied as well. The results showed that linalool, decanal, β-damascenone, hexanal and (E)-2-hexenal were the main volatile compounds of the two cultivars, which meant that the floral, fruity and sweet odour were prominent, followed by the herbaceous aroma. Greenhouse cultivation enhanced herbaceous odour in both ‘Wuhecuibao’ and ‘Zaoheibao’ berries, and reduced the floral aroma, contributed mainly by β-damascenone, in ‘Wuhecuibao’, and the sweet aroma, represented mainly by linalool, in ‘Zaoheibao’. The concentrations of the main aroma compounds were greatly affected by vintage and the intensity of sensorial perception was correspondingly changed, but varietal odour attributes were not significantly altered. These results will not only help promote the cultivation and popularisation of these cultivars, but also will provide valuable data for the use of these cultivars in future breeding.